(untitled) (Altre Modernità, 2016)
One of the features of detective novels in Mexico in 21th Century is the representation of an epistemological crisis. This paper analyzes the relationship between space, the construction of legitimizing discourse and violence against women in La balada de los arcos dorados (2014) by César Silva Márquez (Juarez, 1974). The aim is, on the one hand, to show the way that the geographical area of the desert border of Mexico and the United States provides an episteme and regulates the different practices of the characters and, on the other hand, to emphasize the melancholy, product of an interpretation of current discourse. Hardboiled narrative is a privileged space to discuss this discursive shift and some of the elements of the dominant value system, since the characters are a representation of society, no matter how corrupt they are. The discursive formation that appears in the novel expresses the way in which what can be said is build: spatial redistribution, reconfiguration and movements that allow establishing a truth. These developments have given rise to other lines of a territorial map, ruled by extreme rationality mechanisms to control individuals through the topos as a material form of immaterial. This feature establishes relations between power and knowledge in geography.